Liberalization and tax amnesty in a developing economy (2012)
We show that tax evaders can respond to a tax amnesty, even if enforcement activities do not change, if it is timed to coincide with liberalization and rising incomes. The success of the amnesty, in terms of its effect on tax revenue and welfare, depends on the distribution of the gains from liberalization. Our analysis provides a theoretical justification of the link between successful amnesties and economic liberalization and points to factors that a policy maker should consider for success of future amnesties.